Post COVID‐19 Pulmonary Pseudotumor That Regressed Without Surgery - Nam Vu‐Hoai; Quoc‐Khanh Tran‐Le; Lam Nguyen‐Ho (Respirology Case Reports)
ABSTRACT A cavitary lung mass discovered after SARS‐CoV‐2 infection can represent a benign inflammatory pseudotumor that will regress with watchful follow‐up, thereby sparing the patient an unnecessary surgical resection.